Paham Moderasi Beragama Di Kalangan Masyarakat Perkampungan Mualaf Asli Papua Sorong - Musdalifah, Ririn; Nurfitriani, (Tasamuh: Jurnal Studi Islam, 2025)
This study aims to explore the understanding and implementation of religious moderation values among converts (muallaf) in the indigenous Papuan community who continue their education at IAIN Sorong. The background of this research stems from the dynamics of religious life in the digital era, which requires society to adopt a moderate, open, and tolerant attitude in responding to diversity. This research employed a qualitative approach using interviews, observations, and Focus Group Discussions (FGDs). The participants included community members from Klalin 1 and Maibo Villages, Aimas District, Southwest Papua Province. The findings indicate that the understanding and practice of religious moderation among the muallaf community have been relatively well established. This is reflected in their mutual respect across religious differences, the tradition of visiting each other during major religious celebrations, and openness in social interactions while maintaining their respective faiths. Moreover, local customary values play a significant role as a medium for maintaining interreligious harmony. Thus, religious moderation in the muallaf villages of Papua can be understood as a perspective, attitude, and religious behavior that balances personal conviction with respect for others’ beliefs. These findings highlight that the practice of religious moderation has become an integral part of community life and serves as a crucial foundation for strengthening harmony, tolerance, and unity in Southwest Papua.